2021
DOI: 10.1111/ijfs.15172
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of acid‐soluble collagens from different tissues of large yellow croaker (Larimichthys crocea)

Abstract: Acid-soluble collagens (ASCs) were extracted and characterised from different tissues of large yellow croaker (Larimichthys crocea). The yields of ASCs in bones, skins, scales and muscles were 3.22 AE 0.47%, 42.30 AE 1.15%, 2.82 AE 0.31% and 0.89 AE 0.12%, respectively. SDS-PAGE and ATR-FTIR analysis showed that all ASCs were type I collagen with intact triple helical structure and consisted of α1,3-chain, α2-chain, β-chain and γ-chain. Quantitative analysis of SDS-PAGE revealed that the ratio of β-chains in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
7
2
Order By: Relevance
“…Sun et al . (2021b) reported that the β‐chain intensities were correlated with the thermal stability in fish collagen, which was different from this study results. This difference was possible related to the different sources or extraction procedure.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Sun et al . (2021b) reported that the β‐chain intensities were correlated with the thermal stability in fish collagen, which was different from this study results. This difference was possible related to the different sources or extraction procedure.…”
Section: Resultscontrasting
confidence: 99%
“…The ratio of band intensity of α1/α2‐chains were approximately 2:1 in all LBCs (Fig. 1b), indicating that there existed inter‐ and intra‐molecular cross‐linkages in LBC molecules, which might be positively related to the thermal stability of collagen (Sun et al ., 2021b). Pepsin was able to remove the cross‐linked telopeptide to convert β‐ and γ‐chains to α‐chains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two high-molecular-weight components had weights over 200 kDa. These were identified as a β-chain consisting of two α-chains and a γ-chain consisting of three α-chains, respectively [ 24 ]. In addition, the ratio of α1 and α2 was calculated with Image J software (VERSION 1.8.0, National Institute of Mental Health, Bethesda, MD, USA); specifically, approximately 2:1 was consistent with the molecular structure of type I collagen [α1] 2 α2, thus indicating that the prepared TSC was type I collagen.…”
Section: Resultsmentioning
confidence: 99%